Behavioral Responses of the Snail Lymnaea acuminata towards Photo and Chemo Attractants: A New Step in Control Program of Fasciolosis - Tripathi, Anupam Pati; Singh, V. K.; Singh, D. K. (International Journal of Zoology, 2013)
Fasciolosis is water and food borne disease, caused by Fasciola hepatica and F. gigantica. Snail Lymnaea acuminata is an intermediate host of these flukes. Snail control is one of the major methods to reduce the incidences of fasciolosis. Trapping of snails with the help of photo- and chemoattractants for treatment purposes will be a new tool in control program of fasciolosis. The present study shows that maximum numbers of snails were attracted (52 to 60%), when exposed to photo- and chemostimulant simultaneously, rather than when only chemo- (control) (18 to 24%) or photo- (control) (14 to 19%) stimulus was given. Maximum change in AChE activity in nervous tissue was observed when red monochromatic light was used (258.37% of white light control) as opposed to blue (243.44% of white light control) and orange (230.37% of white light control). The exposure of light directly stimulated the photoreceptors in eye which transmit the signals through nerves to the brain and snail response accordingly. In this signal transmission AChE is one of the important enzymes involved in this process.